To stay within budget, she must use 3.9 gigabytes.
Giving the following information:
Under her cell phone plan, Sofia pays a flat cost of $54.50 per month and $5 per gigabyte. She wants to keep her bill at $ 74 per month.
First, we need to establish the total cost formula:
Total cost= 54.5 + 5*x
x= number of gigabytes
Now, we isolate x:
74= 54.5 + 5x
19.5/5= x
3.9= x
To stay within budget, she must use 3.9 gigabytes
learn more of equation here
brainly.com/question/21316351
#SPJ9
Y = x + 3 is the answer
the y-intercept is 3, so the answer should have a "+ 3" in it
when you are trying to determine the gradient (the x), you can use two methods
first method:
picture/sketch the line. If the line is going upwards (from left to right), it's positive. If the line is going downwards (from left to right), it's negative. However, this method only works for this question, you should try using the second method more
second method:
use the formula: (y - y) / (x - x)
So, you use the y from one of the brackets and subtract the y from the other bracket. Then, you put it over the x ,from the same bracket as the first y, and subtract the x from the second bracket. If you are confused, look at the picture. (Sorry for the messy explanation)
Answer:
is the expression which is equivalent to
.
In other words:
![x\left(2x+3\right)=2x^2+3x](https://tex.z-dn.net/?f=x%5Cleft%282x%2B3%5Cright%29%3D2x%5E2%2B3x)
Step-by-step explanation:
Given the expression
![x\left(2x+3\right)](https://tex.z-dn.net/?f=x%5Cleft%282x%2B3%5Cright%29)
solving
![x\left(2x+3\right)](https://tex.z-dn.net/?f=x%5Cleft%282x%2B3%5Cright%29)
![\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b+c\right)=ab+ac](https://tex.z-dn.net/?f=%5Cmathrm%7BApply%5C%3Athe%5C%3Adistributive%5C%3Alaw%7D%3A%5Cquad%20%5C%3Aa%5Cleft%28b%2Bc%5Cright%29%3Dab%2Bac)
![a=x,\:b=2x,\:c=3](https://tex.z-dn.net/?f=a%3Dx%2C%5C%3Ab%3D2x%2C%5C%3Ac%3D3)
![=x\cdot \:2x+x\cdot \:3](https://tex.z-dn.net/?f=%3Dx%5Ccdot%20%5C%3A2x%2Bx%5Ccdot%20%5C%3A3)
![=2xx+3x](https://tex.z-dn.net/?f=%3D2xx%2B3x)
∴ ![2xx=2x^2](https://tex.z-dn.net/?f=2xx%3D2x%5E2)
Thus,
![x\left(2x+3\right)=2x^2+3x](https://tex.z-dn.net/?f=x%5Cleft%282x%2B3%5Cright%29%3D2x%5E2%2B3x)
Therefore,
is the expression which is equivalent to
.
Answer:
10.50x = 63
You'll divide 63 by 10.50 to get 6 weeks.
Answer:
3
Step-by-step explanation:
Wavelength is usually denoted as letter lambda (λ); it is equal to the speed (v) of a wave train in a medium divided by its frequency (f): λ = v/f. Waves of different wavelengths.
formula: λ = v/f
solution: λ= 30m/s / 10Hz
= 3